Feeding Preferences of the Rearing of Thanasimus formicarius (L.) (Coleoptera, Cleridae) - Özcan, Gonca Ece; Koçoğlu, Nazlı (Alinteri Zirai Bilimler Dergisi, 2018)
Predators have an efficient role on the control of scolytidae (Coleoptera: Curculionidae, Scolytinae) in the biological control. The most common and effective natural enemies of the scolytidae is clerid beetle. Since those natural enemies also feed from the individuals in the different development period of the scolytidae, it is effective for increasing the predation rate of the predator beetle. Besides that, the interaction and preferences between predator beetle-prey have potential importance for the efficacy of control programs. The aim of this study is to determine the feeding preferences of Thanasimus formicarius (L.) (Coleoptera, Cleridae) adults which feed from Ips sexdentatus (Boerner) (Coleoptera: Curculionidae, Scolytinae) adults and larva, quantitatively.. It is determined that the predator beetle consumed the given adult prey and its larva, respectively by the weight of 0-50,79% to 21,43-72,92% and by the feeding customs, 0-66,57% to 50-100% in a one-day period. The differences between the averages of the weights of its adult prey and its larva which the predator consumed is statistically significant and it is determined that predator beetle preferenced for the larva of the prey more than the adults. It is observed that the predations of T. formicarius adults is important on the different development periods of the species I. sexdentatus. As the pressure of the predator with accurate timing decrease the invasion rate, it will also decrease the amount of trees to be harmed.
Keywords: Biological control; Predator beetle; prey interactions; 2. Zero hunger; 14. Life underwater; 15. Life on land; 3. Good health